•Me ajudem por favor.
![Me Ajudem Por Favor class=](https://pt-static.z-dn.net/files/d04/5980efe0a22ae41b5482640d8e465957.jpg)
Resposta:
OLÁ
1)A)
[tex]f(x) = 3x + 1 \\ para \: x = 1 \\ substitui \\ f(x) = 3x + 1 \\ f(1) = 3 \times 1 + 1 \\ f(3) = 3 + 1 \\ \red{f(1) = 4}[/tex]
B)
[tex]f(x) = 3x + 1 \\ para \: x = 0 \\ substitui \\ f(x) = 3x + 1 \\ f(0) = 3 \times 0 + 1 \\ f(0) = 0 + 1 \\ \red{f(0) = 1}[/tex]
C)
[tex]f(x) = 3x + 1 \\ para \: x = -2 \\ substitui \\ f(x) = 3x + 1 \\ f( - 2) = 3 \times ( - 2) + 1 \\ f( - 2) = - 6 + 1 \\ \red{f( - 2) = - 5}[/tex]
D)
[tex]f(x ) = 3x + 1 \\ para \: x = - 3 \\ substitui \\ f(x) = 3x + 1 \\ f( - 3) = 3 \times ( - 3) + 1 \\ f( - 3) = - 9 + 1 \\ \red{f( - 3) = - 8}[/tex]
espero ter ajudado